(untitled) (Hematology Meeting Reports, 2009)
The clinical association of factor VIII (FVIII) deficiency with both hemophilia A and von Willebrand disease (VWF) has been recognized for more than 50 years.1-3 However, the mechanism by which regulated secretion of both proteins occurs, remains controversial.1 Since FVIII is deficient in both hemophilia A and severe von Willebrand disease (VWD), it was not surprising to find that the reason for this observation was that VWF (VWF) served as a carrier protein for FVIII.1 In the absence of VWF, the unbound FVIII is rapidly proteolyzed — a process that reduces its plasma half life from 12 hours to one to two hours. Since patients with severe VWD still had a residual level of FVIII between 3 and 8 IU/dL in the absence of detectable VWF, infusion of VWF resulted in a delayed rise in plasma of FVIII over the subsequent 12 to 24 hours, this was assumed initially to be stimulation of FVIII synthesis, although today, it is recognized that FVIII synthesis is probably progressing normally and it is only in the presence of transfused VWF that the FVIII survival can now normalize and give the clinical picture of the delayed rise in FVIII. The purpose of this review is to establish the basis for how a regulated storage pool, of both VWF and FVIII, is established.